Investigating Peer Interaction in Enhancing English Speaking Skills Among Senior High School Students - Lula Aula Dzukhriyah; Siswana (STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
English speaking ability is a crucial yet challenging skill for students in English as a Foreign Language (EFL) context. This study aims to investigate the impact and specific mechanisms of peer interaction in enhancing English speaking skills among Indonesian senior high school students. Employing a qualitative case study design, data were collected through in-depth, semi-structured interviews with six purposively selected students from a class characterized by frequent peer-based activities. The data were analyzed using thematic analysis involving systematic coding and constant comparative analysis to ensure interpretive rigor. The results indicate that peer interaction exerts a positive holistic impact, with 67% of participants reporting improvements in technical aspects such as fluency, vocabulary acquisition, and grammatical accuracy. Beyond linguistic gains, the analysis revealed that success is driven by an interconnected set of mechanisms. The foundation is Emotional Support in a Supportive Environment, which fosters increased motivation and psychological safety. This dynamic is further enhanced by Motivation Through Interaction Via Competition and put into practice through Active Engagement and Knowledge Exchange Through Feedback, culminating in tangible speaking skill enhancement. The study concludes that peer interaction is an invaluable pedagogical strategy that synergistically combines emotional support and collaborative practices to master a new language.